Investigation of toxicological effects of amorphous silica nanostructures with amine-functionalized surfaces on Vero cells. (January 2019) - Puerari, Rodrigo Costa; Ferrari, Emeline; de Cezar, Martina Garcia; Gonçalves, Renata Amanda; Simioni, Carmen; Ouriques, Luciane Cristina; Vicentini, Denice Schulz; Matias, William Gerson
Abstract: Amorphous silica (SiO2 ) nanostructures are described in the literature as having low toxicity and are widely used in many industrial products. However, surface modifications, such as amine-functionalization, can result in increased cytotoxicity. In this study, amorphous SiO2 nanostructures (SiO2 NS) were synthesized and amine-functionalized with two different amine molecules: primary (SiO2 NS@1) and tri-amine (SiO2 NS@3). The materials were characterized by transmission electron microscopy (TEM), zeta potential (ZP), effective diameter (ED) and surface area measurements, X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). The toxicity of the three SiO2 NS samples toward Vero cells was evaluated. According to the methyl thiazolyl tetrazolium (MTT) assay, the IC50, 24h was 1.477 ± 0.12 g L −1 for SiO2 NS, 0.254 ± 0.07 g L −1 for SiO2 NS@1 and 0.117 ± 0.05 g L −1 for SiO2 NS@3. The order of cytotoxicity was SiO2 NS@3 > SiO2 NS@1 » SiO2 NS. There was an increase in malondialdehyde (MDA) levels and ROS productions in the cells exposed to all three materials. Also, TEM images showed damage on the mitochondria and rough endoplasmic reticulum. Highlights: Amine-functionalization of SiO2 NS enhanced the cytotoxicity toward Vero cells. SiO2 NS entered the Vero cells and promoted ROS production and lipid peroxidation. Evidence of Trojan horse effect was observed after SiO2 NS amine-functionalization. Mitochondria and endoplasmic rough damages were observed after exposure to SiO2 NS.